PELATIHAN DAN PENDAMPINGAN DIGITAL MARKETING BAGI PELAKU USAHA KULINER DI KOTA BIREUEN - munirul ula; Rizal Tjut Adek; Muhammad Muhammad; Bustami Bustami; Fasdarsyah Fasdarsyah; Mukhlis Mukhlis (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
During the Covid-19 disaster, the condition of Micro, Small and Medium Enterprises (MSMEs) in Bireuen Regency was very alarming. The impact of the pandemic outbreak and regulations related to the Enforcement of Restrictions on Community Activities have caused sales turnover to decline, therefore culinary entrepreneurs are required to be more creative and innovative in conducting marketing activities. Digital marketing activities is one solution to increase sales during this pandemic. However, there are still many culinary business actors in Bireuen Regency who have not mastered digital marketing strategies. Therefore, digital marketing training and assistance is needed for culinary entrepreneurs in Bireuen Regency to be able to compete and innovate to increase sales turnover in this pandemic era. This Digital Marketing Training and Assistance aims to provide knowledge and skills for entrepreneurs in Bireuen Regency to increase sales through digital marketing. The results of the evaluation of this service activity are very useful for increasing the knowledge and expertise of participants in online marketing. Through this training and mentorship activity, culinary business actors in Bireuen Regency can improve social media marketing, generate marketing material to assist digital marketing, and raise sales turnover.